Admiralty jurisdiction in Namibia since 1920 - Ndauendapo, Gervasius Nate (Institute of Marine and Environmental Law, 2026)
The aim of this dissertation is to look at the development of admiralty jurisdiction and practice in Namibia since 1920. It will look at how a colonial piece of legislation, namely, the Colonial Courts of Admiralty of 1890 became part of Namibia. It will look at how the Namibian government attempts to update and modernize its laws relating to Admiralty jurisdiction and practice. Namibia became independent on the 21st of March 1990. Before independence Namibia was ruled by South Africa since 1921. Initially Namibia was a colony of Germany since 1884. When Germany was defeated at the end of World War 1, Namibia was transferred by the then League of Nations to South Africa as a C-mandate. South Africa was to administer Namibia until such time as the country was ready for independence. When the United Nations ended South African mandate over Namibia, South Africa refused to out of Namibia. It took a long and bloody war to convince South Africa to pull out of Namibia. On the 21st of March 1990 Namibia became independent, through out the period of occupation South African laws applied to Namibia.